Bloom : Words by Kyo Maclear, Pictures by Julie Morstad - Maclear, Kyo, 1970-; Morstad, Julie (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2018)
By the 1930s Elsa Schiaparelli had captivated the fashion world in Paris, but before that, she was a little girl in Rome who didn't feel pretty at all. Bloom: a story of fashion designer Elsa Schiaparelli is the enchanting story for young readers of how a young girl used her imagination and emerged from plain to extraordinary.
Ages 4-8.
Keywords: Schiaparelli, Elsa, -- 1890-1973 -- Juvenile literature; Fashion designers -- Italy -- Biography -- Juvenile literature; Women fashion designers -- Biography -- Juvenile literature; Costume design -- History -- 20th century -- Juvenile literature